Development of a multi-slit virtual impactor as a high-volume bio-aerosol sampler - 육세진 (SEPARATION AND PURIFICATION TECHNOLOGY, 2020)
Virtual impactors are capable of aspirating aerosols in the air, concentrating particles of a certain size, and discharging these particles through a minor flow. In general, commonly used virtual impactor has a cut-off size of 1 μm or more, a concentration ratio of 10–20 times, and an operating flowrate of 10 L/min; it is used to increase the detection probability of various aerosol measuring equipment. In this study, we developed a special-purpose virtual impactor aimed at the mass capturing of aerosols, including pathogens released by human respiration or coughing. For this purpose, we designed a virtual impactor exceeding the typical operating range, with a cut-off size of 0.3 μm and a concentration ratio of 13.3. Five multi-slit nozzles were adopted to indicate a cut diameter of 0.3 μm for a high aerosol flowrate of 170 L/min. Clean air was injected near the nozzle wall of the virtual impactor to minimize wall loss and further reduce the cut-off size. The performance of the designed virtual impactor was verified through numerical analyses and experimentation. As a result, aerosol aspirated at 170 L/min of flowrate was effectively concentrated in the minor flow with a cut-off size of 0.3 μm.
Keywords: Virtual impactor; Slit nozzle; Collection efficiency; Clean air; Wall loss